2000
DOI: 10.1021/om9909946
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Density Functional Study of Associative and Dissociative Mechanisms in the Rhodium(I)-Catalyzed Olefin Hydroboration Reactions

Abstract: The [RhCl(PH3)2]-catalyzed hydroboration reaction C2H4 + HBR2 → H3CCH2BR2 (R = OH, 2R = OCHCHO) was investigated by means of density functional theory type calculations using the Amsterdam density functional (ADF) program. In the first step, the borane adduct [RhCl(η2-HBR2)(PH3)2] (1) forms from [RhCl(PH3)2] and the borane HBR2. Subsequently, C2H4 adds to 1 to give either [RhClH(BR2)(C2H4)(PH3)2] (2) (associative pathway I) or [RhCl(η2-HBR2)(C2H4)(PH3)] (23) (dissociative pathway II). Further branching arises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
52
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 25 publications
4
52
0
Order By: Relevance
“…The hydride and boryl ligands are trans in the reactive form of this complex. [52] Subsequent migratory insertion of the alkene into the rhodium-hydride bond produces the regioisomeric alkyl boronate esters 7 and 8. Upon reductive elimination these give the anti-Markovnikov product 9 or the Markovnikov product 10, respectively, and the catalytic species 4 is regenerated.…”
Section: Mechanism Of Rhodium-catalysed Hydroborationmentioning
confidence: 99%
See 3 more Smart Citations
“…The hydride and boryl ligands are trans in the reactive form of this complex. [52] Subsequent migratory insertion of the alkene into the rhodium-hydride bond produces the regioisomeric alkyl boronate esters 7 and 8. Upon reductive elimination these give the anti-Markovnikov product 9 or the Markovnikov product 10, respectively, and the catalytic species 4 is regenerated.…”
Section: Mechanism Of Rhodium-catalysed Hydroborationmentioning
confidence: 99%
“…[53] Theoretical studies have suggested that reductive elimination is the slowest step in the overall transformation. [51,52] Among efforts to elucidate the exact mechanism, Evans has proposed on the basis of deuterium labelling studies that certain steps in the catalytic cycle, namely olefin binding to the rhodium catalyst, as well as subsequent hydride migration, are reversible. However, the level of reversibility is highly substrate-dependent.…”
Section: Mechanism Of Rhodium-catalysed Hydroborationmentioning
confidence: 99%
See 2 more Smart Citations
“…94 A related study on the hydrosilylation of alkenes (see Hydrosilation Catalysis) using RhCl(PH 3 ) 3 as a catalyst model supports the modified Chalk -Harrod mechanism, namely oxidative addition of the Si-H bond to the metal followed by alkene coordination, insertion of the alkene into the Rh-Si bond, and C-H reductive elimination.…”
mentioning
confidence: 95%